The role of Islamic banks in developing a sharia-based economy in the digital era in Indonesia - Irawan, Heri (Journal of Islamic Economics Lariba, 2023)
IntroductionThe financial industry, including Islamic banks, has been significantly affected by the digital era in Indonesia. Islamic banks operate based on Islamic Sharia principles, offering banking services that comply with Islamic law such as the prohibition of usury (interest) and other Sharia principles. They provide various types of financing, including mudharabah and musyarakah, as well as financial products, such as savings accounts, current accounts, and deposits.ObjectivesThis study examines the role of Islamic banks in developing a sharia-based economy in Indonesia, focusing on the challenges and opportunities presented by the digital era. MethodThis study uses a literature review to investigate the role of Islamic banks in the development of a sharia-based economy. This research involves searching, processing, and analyzing data from various relevant and reliable literature sources. Thematic analysis was used to identify patterns and key themes based on previous research findings.ResultsIslamic banks play a crucial role in sharia-based economic development and contribute significantly to Indonesia's economic growth. They enhance the investment sector through third-party funds (DPK) and increase financing through the distribution of funds to the public (PYD). Shariah principles, such as murabahah, mudharabah, and musyarakah, form the basis of financing offered by Islamic banks. Key opportunities include increased accessibility, product innovation and operational efficiency. However, challenges such as Shariah compliance, customer awareness, and cybersecurity were also analyzed. ImplicationsThe results suggest that Islamic banks can design strategies to optimize the benefits of the digital era while addressing its challenges. The findings emphasize the importance of adapting to digital advancements to maintain competitiveness and relevance in the financial industry.Originality/NoveltyThis study provides insights into the integration of Islamic principles with modern banking practices in the digital era. This highlights the dynamic role of Islamic banks in promoting economic growth while adhering to Sharia principles.